Customer satisfaction analysis on general banking of Social Islami Bank Limited (SIBL) - Rahman, Sinthia (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.